Behavioural and functional changes in neglect after multisensory stimulation. Issue 5 (28th May 2022) - Làdavas, Elisabetta; Tosatto, Luigino; Bertini, Caterina
ABSTRACT: The present cohort study investigated whether systematic multisensory audio-visual stimulation might improve clinical signs of neglect. To this aim, patients with neglect ( n  = 7) and patients with neglect associated with hemianopia ( n  = 12) were exposed to a course of audio-visual stimulation with spatially and temporally coincident audio-visual pairs of stimuli for 10 daily training sessions (4 h of training per day), over two weeks. Performance on neuropsychological tests assessing neglect was measured before training, immediately after the training and months after the training at a follow-up session. The results showed significant post-training improvements in clinical signs of neglect, which were stable at the follow-up. These findings suggest that intensive and prolonged multisensory audio-visual stimulation affects orientation towards the neglected hemifield, therefore inducing long-term improvements in visual exploration and neglect symptoms in both patients with neglect and patients with neglect associated with hemianopia. Previous evidence from hemianopic patients suggests that these post-training effects might be mediated by activity in spared subcortical structures, such as the superior colliculus, which are relevant to multisensory integrative processing and spatial orientation.